The - Fine, Perry G. (Oxford University Press, 2008)
The Hospice Companion is designed to promote, establish, maintain and continuously improve comprehensive systems of care that ensure the highest quality of services to meet the needs of patients and their families during the last phase of life. On behalf of their patients, all hospice providers must inculcate processes of care that lead to maximal comfort and functional capacities, and a sense of being valued throughout the final stages of any chronic and progressive illness. The values embodied in The Hospice Companion reflect a commitment to these premises: -The dying patient's achievable goals are the highest priority of care